2011
DOI: 10.4137/cmamd.s7773
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Changes in Patients with Recent-Onset Rheumatoid Arthritis

Abstract: Background:Osteoporosis and related fragility fractures are one of the most common complications seen in patients with rheumatoid arthritis (RA) and dramatically affect quality of life.Objective:To evaluate changes in bone mineral density in patients with recent onset rheumatoid arthritis (<1 year) and its correlation if any with a modified DAS-28 score and simple erosion narrowing score (SENS).Methods:This study included 30 patients with recent-onset rheumatoid arthritis fulfilling the new American College of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
1
16
2
Order By: Relevance
“…This is in agreement with another study that has evaluated BMD and disease activity in RA patients as done in Birmingham 1996. Our finding did not match with the study done in Cairo, Egypt 2011 27 which state that BMD changes do occur in patients with early RA, and are not necessarily correlated with disease activity (DAS-28). It is important to mention that disease duration of more than five years is associated with bone loss in particular at FN regardless of treatment.…”
Section: Resultscontrasting
confidence: 99%
“…This is in agreement with another study that has evaluated BMD and disease activity in RA patients as done in Birmingham 1996. Our finding did not match with the study done in Cairo, Egypt 2011 27 which state that BMD changes do occur in patients with early RA, and are not necessarily correlated with disease activity (DAS-28). It is important to mention that disease duration of more than five years is associated with bone loss in particular at FN regardless of treatment.…”
Section: Resultscontrasting
confidence: 99%
“…In 30 Egyptian RA patients (aged 35.7 years), osteopenia and osteoporosis were reported in 50% and 13.3%, respectively. [ 11 ] In a Finnish study in premenopausal women with RA ( n = 78), mean LS BMD was 1.157 g/cm 2 , which is slightly higher to that observed in our patients (1.05 g/cm 2 ). [ 12 ] In a Korean study involving 234 RA patients (aged 60 years), osteopenia and osteoporosis were observed in 52% and 39%, respectively.…”
Section: Discussioncontrasting
confidence: 52%
“…Nevertheless, in our study, osteoporosis at all sites was more common in females than in males, without any statistically significant intergroup difference. Furthermore, in the study of Yoon J et al and in similar studies, gender of the patients was significantly associated with osteoporosis (13) . Spine was the most common site of osteoporosis in patients with RA with BMD of 16 %, followed by hip with BMD of 12%.…”
Section: Discussionmentioning
confidence: 72%